To Improve Teacher Effectiveness and Student Ability by Digitized Assessment Technology with Facilitating OBE: Examining the Impact of Computerized Assessment on Student Motivation and Performance in ICT Courses (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Earlier research has found that computer based assessments (CBA) have many valuable effects on learning outcome (LO) of students. This study examines the impact of computerized assessment on the underlying motivation and performance of students effectively in ICT (Information Communication Technology) courses. Digitized method of assessments provides meticulous information to both students and facilitator that helps to improve student learning and effectiveness in teaching (Angelo, 1991). In this paper, we try to compare the curriculum of MCA in the state of Tamilnadu, in India with the components of OBE followed in various developing countries. The proposed method shows that the students exposed to frequent computer based assessments had definitely gained higher levels in using technology, learning skill, creativity, independence, and overall motivation compared to other students.